A= ($\frac{3}{√x-1}$ +$\frac{√x+3}{x-1}$) B= ($\frac{x+2}{x+√x-2}$- $\frac{√x}{√x+2}$ ) (x ≥0,x khác 1) a) rút gọn M=A:B b)Tìm Gtri lớn nhất của M

Question

A= ($\frac{3}{√x-1}$ +$\frac{√x+3}{x-1}$)
B= ($\frac{x+2}{x+√x-2}$- $\frac{√x}{√x+2}$ ) (x ≥0,x khác 1)
a) rút gọn M=A:B
b)Tìm Gtri lớn nhất của M

in progress 0
Brielle 2 tháng 2021-07-18T20:01:48+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-07-18T20:02:51+00:00

    Đáp án:

    $\begin{array}{l}
    a)M = A:B = \left( {\frac{3}{{\sqrt x  – 1}} + \frac{{\sqrt x  + 3}}{{x – 1}}} \right):\left( {\frac{{x + 2}}{{x + \sqrt x  – 2}} – \frac{{\sqrt x }}{{\sqrt x  + 2}}} \right)\\
     = \frac{{3\left( {\sqrt x  + 1} \right) + \sqrt x  + 3}}{{\left( {\sqrt x  + 1} \right)\left( {\sqrt x  – 1} \right)}}:\left[ {\frac{{x + 2}}{{\left( {\sqrt x  + 2} \right)\left( {\sqrt x  – 1} \right)}} – \frac{{\sqrt x }}{{\sqrt x  + 2}}} \right]\\
     = \frac{{4\sqrt x  + 6}}{{\left( {\sqrt x  + 1} \right)\left( {\sqrt x  – 1} \right)}}:\frac{{x + 2 – \sqrt x \left( {\sqrt x  – 1} \right)}}{{\left( {\sqrt x  + 2} \right)\left( {\sqrt x  – 1} \right)}}\\
     = \frac{{4\sqrt x  + 6}}{{\left( {\sqrt x  + 1} \right)\left( {\sqrt x  – 1} \right)}}.\frac{{\left( {\sqrt x  + 2} \right)\left( {\sqrt x  – 1} \right)}}{{\sqrt x  + 2}}\\
     = \frac{{4\sqrt x  + 6}}{{\sqrt x  + 1}}\\
    b)x \ge 0;x \ne 1\\
    M = \frac{{4\sqrt x  + 6}}{{\sqrt x  + 1}}\\
     = \frac{{4\sqrt x  + 4 + 2}}{{\sqrt x  + 1}}\\
     = 4 + \frac{2}{{\sqrt x  + 1}}\\
    Do:\sqrt x  \ge 0\forall x \ge 0;x \ne 1\\
     \Rightarrow \frac{1}{{\sqrt x  + 1}} \le 1\forall x \ge 0;x \ne 1\\
     \Rightarrow 4 + \frac{2}{{\sqrt x  + 1}} \le 6\forall x \ge 0;x \ne 1\\
     \Rightarrow M \le 6\forall x \ge 0;x \ne 1\\
     \Rightarrow GTLN:M = 6 \Leftrightarrow x = 0
    \end{array}$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )